INTEGRASI ADAT DAN SYARIAH (Ahkam: Jurnal Hukum Islam, 2022)
This study intends to describe the religious meaning of Pasang Bundel tradition in marriage ceremonies in the Besole Village community, Besuki District, Tulungagung Regency, East Java. This research is qualitative research, where data collection was done by observation and in-depth interviews. The data were analyzed using the inductive method to get a conclusion. From this research, it was found that first, the tradition of Pasang Bundel is the tradition of using offerings at weddings. Attach means to install Cokbakal (offerings) with banana leaves as the container, on each side of the container, a pair of Janur (yellow young coconut leaves) is shaped into a cone. The container contains seven kinds of flowers, one free-range chicken egg, a small glass tied with rawe (a type of white thread), incense, badhek water (water soaked in white glutinous rice) and a coin. Cokbakal was placed by traditional leaders in the yard, every corner of the house, bathroom and kitchen. The Bundel means slametan (a ritual of praying and giving thanks to God Almighty). This event was held with relatives and neighbors where after the ceremony is over they are given a berkatan (a container of food). Second, the symbolic meaning of the Pasang Bundel tradition is as an expression of gratitude from the person who carries out the ceremony to God Almighty and as a means to offer a prayer so that the wedding ceremony can run smoothly and without obstacles. This tradition Pasang Bundel integrated adat (Custom) and sharia where some items and rituals originating from local customs are integrated with things that have Islamic nuances. Third, this Pasang Bundel tradition is carried out for religious, social purposes, and ancestral customs preservation.